Interplay between cytochrome c and gibberellins during Arabidopsis vegetative development - Racca, Sofía; Welchen, Elina; Gras, Diana E; Tarkowská, Danuše; Turečková, Veronika; Maurino, Veronica G; Gonzalez, Daniel H (The Plant journal, 2018)
We studied the effect of reducing the levels of the mitochondrial electron carrier cytochrome c (CYTc) in Arabidopsis thaliana. Plants with CYTc deficiency have delayed growth and development, and reach flowering several days later than the wild-type but with the same number of leaves. CYTc-deficient plants accumulate starch and glucose during the day, and contain lower levels of active gibberellins (GA) and higher levels of DELLA proteins, involved in GA signaling. GA treatment abolishes the developmental delay and reduces glucose accumulation in CYTc-deficient plants, which also show a lower raise in ATP levels in response to glucose. Treatment of wild-type plants with inhibitors of mitochondrial energy production limits plant growth and increases the levels of DELLA proteins, thus mimicking the effects of CYTc deficiency. In addition, an increase in the amount of CYTc decreases DELLA protein levels and expedites growth, and this depends on active GA synthesis. We conclude that CYTc levels impinge on the activity of the GA pathway, most likely through changes in mitochondrial energy production. In this way, hormone-dependent growth would be coupled to the activity of components of the mitochondrial respiratory chain.
Keywords: Cytochromes c; Mitochondria; proteiny huseníčku; gibberellin; mitochondrion; cytochromy c; Gibberellins; Arabidopsis thaliana; Arabidopsis Proteins; gibereliny; mitochondrie; regulace genové exprese u rostlin; glukosa; Gene Expression Regulation, Plant; DELLA protein; Arabidopsis; Energy Metabolism; škrob; Starch; energetický metabolismus; homeostáza; Glucose; Homeostasis; cytochrome c